Perioperative Komplikationen des unteren Gastrointestinaltraktes: Prävention, Erkennung, Therapie = Perioperative complications of the lower gastrointestinal tract : prevention, recognition and treatment - Kulu, Yakup; Büchler, Markus W.; Ulrich, Alexis (Der Chirurg, 2015)
Perioperative complications following surgical procedures of the lower gastrointestinal tract still represent a relevant problem. The perioperative morbidity may negatively affect short and long-term outcomes of treatment of individual patients. The additional diagnostics and treatment required also lead to additional costs that burden the healthcare system. Ideally, complications should be avoided by preventive measures. In the event of a complication, early detection is essential for appropriate treatment.Surgical site infections (SSI) have been described as the most common complication in the postoperative period and may occur in up to 30 % of cases. Through various perioperative measures up to 40-60 % of SSI are preventable. Depending on the location, the reported anastomotic leakage rate ranges from 1 % to 23 %. The therapeutic strategy ranges from conservative measures through interventional methods up to surgical revision. An early postoperative burst abdomen occurs in about 3 % of cases. A midline closure with small stitches and small suture distances (suture length to wound length ratio of 4) seems to be superior to large stitches with long distance intervals. A rare but potentially fatal complication is bleeding. The identification of patients with relevant risk factors is of great importance. This article summarizes the prevention, recognition and treatment of perioperative complications after surgery of the lower gastrointestinal tract.